Bioconcentration Lead (Pb) Green Mussel (Perna viridis) in Semarang Bay - Lahati, Sonny; Hartoko, Agus; Haeruddin, Haeruddin (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
The coastal waters of Semarang Bay have been polluted by heavy metal lead (Pb). The research was conducted from September 2015 to March 2016 with 3 stations at the Tambaklorok green mussel cultivation location. Analysis of the concentration of heavy metal Pb using the AAS (Atomic Absorption Spectrophotometer) method. Data processing using SPSS and Excel. The results showed that the average concentration of heavy metal Pb in the air ranged from 0.51 to 0.76 mg/L. The average concentration of heavy metal Pb in three observations obtained an average concentration of Pb between 4.975-20.43 mg/kg. Green mussels taken in the waters were sorted and separated according to the length of the shell and weighed 1 kg each according to the length of the shell. Small (2-3 cm), medium (3-4 cm) and large shells with long shells (5-6 cm). The results of the measurement of the concentration of heavy metal Pb in P. viridis showed that the average green mussel shell size 4-5 cm at the location of station III had the lowest concentration of heavy metal Pb at 0.24 mg/kg. Meanwhile, the highest average concentration of Pb in P. viridis was found at station I at 0.89 mg/kg with a shell length of 2-3 cm. The correlation equation between shell length and Pb concentration is Y= - 0.131 + 1.13 X. Standard error of the Estimate (SEE) is 0.19. While the standard deviation of 0.20 means that the predictor variable (water) to predict the dependent variable (shellfish) is feasible because SEE is greater than the standard deviation. The average value of the Bioconcentration Factor (BCF) of green mussels is smaller than that of medium-sized green mussels and large green mussels. Green mussels can be consumed by someone if the body weight is 60 kg, then as much as 5.8 kg in a week because it contains Pb.